Le transfert des littératures francophones en(tre) périphérie Pratiques de sélection, de médiation et de lecture - Cedergren, Mickaëlle (Stockholm Studies in Romance Languages, 2023)
This study focuses on the circulation, mediation and interpretation of French-speaking literature, no longer circulating towards the center but towards the periphery. In this book, Sweden is an example of a case of non-French-speaking periphery from which the analyzes are carried out. This starting point has made it possible to reconsider the scope of literature from decentralized French-speaking geographical areas (known as peripheral) and to highlight the negotiation practices at work by the non-French-speaking periphery. By evaluating the visibility and the resemantization of these literatures on the one hand, outside the center and on the other hand, outside the French-speaking literary system, this book has brought new knowledge on the functioning of the literary transfer of French-speaking literatures outside of the French-speaking literary system. The ambition of this book has thus made it possible to (re)define the positioning and the degree of autonomy of the periphery, both Swedish and French-speaking, in relation to the Parisian center by studying the literary exchanges between Sweden and the French-speaking literary system. To achieve this goal, this research proceeds in three stages, inspired by Bourdieu's tripartite model to present a) the selection of literature translated from French into Swedish and the distribution of French-language literature in the journalistic press b) the mediating methods with which cultural agents operate and c) the representations of critical reading at work in newspapers. This project focused on the production, mediation and reception of French-speaking literature in Sweden is structured around four major studies. The three in-depth chapters (IV, V and VI) respectively deal with mediators (press actors and translators) and the analysis of the two most significant geographical areas in our data (French-speaking North Africa and Europe). of the French-speaking West). These three studies are in turn based on the analysis of production and distribution flows, carried out using all the quantitative data collected in translation and journalistic reception during the study period (1989-2019). By relying on a set of cross-sectional studies, this book examines the literary circulation of literature from peripheral French-speaking geographical areas and manages to draw conclusions that have remained invisible until now. In conclusion, three different major types of strategies emerged: a) selection practices called positioning strategies, b) mediation practices called configuration strategies and finally 3) reading practices or legitimation strategies. After observing the differences in treatment between the French-speaking literatures of the North and the South, the study ends by setting out some future proposals for the study of the transfer of French-speaking literatures to non-French-speaking peripheries. This kind of analysis contributes to rebalancing the place of French-speaking literatures in the world and shows the continual displacements and repositionings at work in which the margins of the French-speaking world, where non-French-speaking peripheral territories are part, can participate.